2008
DOI: 10.1093/molehr/gan051
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin signalling in primary cultures of human myometrial cells

Abstract: In myometrium of pigs and rats, though not humans, relaxin appears to mediate an inhibition of spontaneous and oxytocin-induced contractility, presumably acting through a G-protein coupled receptor (RXFP1) to generate cAMP. In humans, circulating relaxin is highest in the first trimester, including the time of implantation, when transitory uterine quiescence could help a blastocyst to implant. We investigated whether relaxin can activate adenylate cyclase in primary human myometrial cells from non-pregnant tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…Additionally, in the rat it has been shown that relaxin acting on the myometrium may be involved in spacing of embryos in multiparous species (Rogers et al, 1983). In the human, relaxin does not appear to have any effect to inhibit spontaneous or oxytocin-induced contractility (MacLennan et al, 1986), although we have recently shown that human myometrial cells obtained at routine hysterectomy do indeed respond via RXFP1 to relaxin, and just like hESC cultures generate cAMP in a tyrosine kinase-dependent manner (Heng et al, 2008).…”
Section: Relaxin and The Endometrium In Early Pregnancymentioning
confidence: 73%
See 4 more Smart Citations
“…Additionally, in the rat it has been shown that relaxin acting on the myometrium may be involved in spacing of embryos in multiparous species (Rogers et al, 1983). In the human, relaxin does not appear to have any effect to inhibit spontaneous or oxytocin-induced contractility (MacLennan et al, 1986), although we have recently shown that human myometrial cells obtained at routine hysterectomy do indeed respond via RXFP1 to relaxin, and just like hESC cultures generate cAMP in a tyrosine kinase-dependent manner (Heng et al, 2008).…”
Section: Relaxin and The Endometrium In Early Pregnancymentioning
confidence: 73%
“…It may also activate the alternative receptor RXFP2 (which is specific for INSL3), but only in some species such as the human, and then only at highly supraphysiological concentrations. In transfected cells, and in some naturally receptor-expressing primary cells, such as human endometrial stromal cells (Bartsch et al, , 2004Ivell et al, 2007) or human myometrial cells (Heng et al, 2008), relaxin interacts with RXFP1 to activate G s -mediated adenylyl cyclase causing an elevation of intracellular cAMP. It may also in some circumstances activate PI3-kinase in a G i/o -dependent manner involving PKC-zeta (Nguyen and Dessauer, 2005).…”
Section: Relaxin and Ovarian Functionmentioning
confidence: 99%
See 3 more Smart Citations